The Evaluation of Noninvasive Mechanical Ventilation Efficacy in Two Types of Acute Respiratory Failure - Tezcan, Busra; Turan, Sema; Kazanci, Dilek; Bektas, Serife; Yazicioglu, Hija; Ergun, Berna; Bolukbasi, Demet; Erdemli, Ozcan (GALENOS YAYINCILIK, 2017)
Objective: Noninvasive mechanical ventilation (NIMV) decreases the incidence of endotracheal intubation and complications related to the endotracheal intubation in acute respiratory failure. However, there is some concern that it can increase mortality due to the delay of endotracheal intubation. We aimed to evaluate the efficacy of NIMV in acute pulmonary edema (APE) and postoperative respiratory failure (PORF) patients. Materials and Methods: Records of 100 NIMV assisted patients suffering from APE and PORF were evaluated, retrospectively, for a period from Jan 01, 2011 to Dec 15, 2012. The patients were divided into two groups as APE (group 1

n=59) and PORF (group 2

n=41) patients. The demographic data of the patients having a frequency of endotracheal intubation after NIMV, the time between initiation of NIMV and intubation, ejection fraction (EF), systolic pulmonary arterial pressure, APACHE II scores, intensive care unit/hospital length of stay and mortality rate were recorded. Results: There were no significant differences between the groups in terms of endotracheal intubation incidence and the time between initiation of NIMV and intubation. The intubated patients had a longer length of hospitalization and stay in intensive care unit, higher baseline APACHE II scores, and mortality rates compared to nonintubated patients in both groups. The patients with chronic obstructive pulmonary disease in group 1 and with lower EF in group 2 were more likely to be intubated. Conclusion: In this study, we observed that higher baseline APACHE II scores were associated more with a high mortality rate than the extension of time between NIMV and endotracheal intubation in patients with two different acute respiratory failures, like APE and PORF.
Keywords: Noninvasive mechanical ventilation; postoperative respiratory failure; acute pulmonary edema; atelectasis